2016
DOI: 10.4025/cienccuidsaude.v15i2.29262
|View full text |Cite
|
Sign up to set email alerts
|

<b>O cuidado de enfermagem à pessoa com doença falciforme em unidade de emergência/ Nursing care to people suffering with sickle cell disease in emergency unit <b>

Abstract: Este estudo objetivou identificar como a equipe de enfermagem percebe o cuidado à pessoa com doença falciforme na unidade de emergência. Trata-se de um estudo qualitativo e descritivo, desenvolvido em um hospital especializado no Rio de Janeiro com 12 membros da equipe de enfermagem do referido setor. A produção de dados ocorreu entre abril e setembro de 2014, mediante entrevista semiestruturada. Os dados foram submetidos à análise de conteúdo, emergindo como categoria: A equipe de enfermagem no cuidado à pess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 4 publications
0
4
0
2
Order By: Relevance
“…Thus, it is understood that SCD in men has specificities, as it hinders their participation in the world of work, weakening the role of home provider and autonomous and invulnerable man. It also interferes with subjectivity, as it distorts body image, resulting in changes in clothing, interpersonal relationships, leisure, life projects and sexuality ( 18 , 19 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is understood that SCD in men has specificities, as it hinders their participation in the world of work, weakening the role of home provider and autonomous and invulnerable man. It also interferes with subjectivity, as it distorts body image, resulting in changes in clothing, interpersonal relationships, leisure, life projects and sexuality ( 18 , 19 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, SCU treatment is slow and takes a long time to heal, with high rates of recurrences. Therefore, to treat it, health professionals must base themselves on scientific evidence and develop technical skills that guide conduct ( 19 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In the power relations established between healthcare workers and people in illness, there is an expectation of professionals to discipline and docile the bodies. The more the user complains about more drugs or criticizes the professional's action for not giving them measures capable of reducing suffering, the more they are labeled and discriminated against (29) . In this study, people with SCD revealed receiving discourteous and negligent treatment in painful crises.…”
Section: Discussionmentioning
confidence: 99%
“…The author affirms that the following characteristics justify this argument: (1) This disease affects millions of people worldwide; (2) It has a more significant impact on impoverished populations; (3) It has a high morbidity and mortality rate; (4) It can act in comorbidity with other equally lethal diseases; (5) It is simple to diagnose and (6) It can be treated with low-cost options. There is still insufficient data on mortality from SCD in Brazil [33][34][35] , and more studies addressing this population's aging and the most frequent complications are required.…”
Section: ) Historical and Current Neglect And The Impact Of Racism On...mentioning
confidence: 99%